The Effectiveness of Postpartum Maternal and Child Nutrition Health Services at Waiwerang Community Health Center, East Flores Regency - Benga Aran, Marselina; Mustofa, Amirul (Departemen Ilmu Administrasi FISIP UNHAS, 2023)
This study evaluates the effectiveness of postpartum maternal and child nutrition health services at the Waiwerang Community Health Center (CHC) in East Flores Regency, Indonesia. Using a qualitative descriptive approach supported by interviews and field observations, the research captures insights from both health workers and service users within the CHC in East Adonara District. The findings indicate that the overall quality of postnatal nutrition services is perceived as effective, particularly in terms of service accessibility, staff responsiveness, and basic nutrition counseling. However, the study also identifies areas requiring improvement, such as the technical performance and capacity-building of nutrition officers, which are critical to sustaining service quality and meeting national health standards. This research highlights the importance of strengthening public health governance at the local level, particularly in underserved and remote regions. It underscores the role of institutional accountability, professional development, and community engagement in enhancing the delivery of essential maternal and child health services. These insights contribute to broader policy efforts aimed at improving decentralized public health systems in developing country contexts.